The clues offered by SNAREs on the vacuoles of plants and animals - Barozzi, Fabrizio; Sampaio, Miguel; Pereira, Cláudia; Di Sansebastiano, Gian Pietro (Frontiers in Plant Science, 2025)
Vacuoles and lysosome-related organelles (LROs) are essential compartments in eukaryotic cells playing crucial roles in storage, degradation, signaling, and homeostasis. Despite their functional similarities, these organelles have traditionally been studied in isolation within plant and animal cell biology. This review bridges these disciplines by exploring the molecular parallels between plant vacuoles and animal LROs, with a particular emphasis on the SNARE (Soluble N-ethylmaleimide-sensitive factor Attachment Protein Receptor) protein family, which governs membrane fusion and trafficking. SNARE complexes orchestrate intracellular transport ensuring the correct delivery of cargo to vacuoles and LROs. By analyzing SNARE homologs and their interactions across kingdoms, we highlight conserved mechanisms that regulate organelle biogenesis, remodeling, and function. This comparative approach not only advances our understanding of cellular compartmentalization but also sheds light on potential applications in biotechnology, stress adaptation, and human disease research. Integrating knowledge from plant and animal systems offers a powerful framework for discovering novel regulatory pathways in membrane trafficking and cellular homeostasis.